The Iberian electricity market: analysis of the risk premium in an illiquid market - Ferreira, Márcio (2018)
This paper analyzes the risk premium in the base-load monthly futures contracts traded on the Iberian electricity market (MIBEL) between July 1, 2006 and March 31, 2017. During this time span, the ex post risk premium on the last trading day presented a relative mean value of 5:77% as well as negative skewness, excess kurtosis and some persistence. The risk premium depended on the season of the year, with the absolute value for winter futures being more than five times higher than for summer futures. The absolute risk premium and its volatility decreased nonlinearly throughout the remaining trading days until maturity. There is no statistical evidence for rejecting an unbiased forward hypothesis; however, the sequence of futures prices approaching maturity showed some predictive power as regards the risk premium. The futures price path between seven and three days prior to delivery explained around 28% of the variability in the risk premium, and there is some evidence that this information can be used to successfully forecast the risk premium signal.